A Cor da Lua: cenografia teatral, trajetória e dispositivo poético-pedagógico - Herrero, Daniel Freitas (2025)
The present research aims to develop an autobiographical reflection that intertwines the theoretical foundations of scenography, a critical analysis of my trajectory as a scenographer, and a proposal for the use of scenography as a poetic-pedagogical device. The initial study focuses on the discussion of scenographic concepts, investigating its role and relevance as a constitutive element of the theatrical experience. Subsequently, I present accounts of various projects I have carried out in scenography, highlighting the challenges faced, the creative solutions adopted, and the lessons learned throughout the process. This approach enables an understanding of the technical and artistic aspects that have shaped my practice as a scenographer. Drawing on this consolidated experience, the research culminates in the prospect of an experimental performance entitled The Color of the Moon. This is an original creative process in which scenography takes on the role of central protagonist, configured as a poetic-pedagogical device designed to provide the audience with a formative experience through an immersive and sensory atmosphere.